EVALUASI PENGELOLAAN BANTUAN SOSIAL DI DESA PENTADIO BARAT KECAMATAN TELAGA BIRU KABUPATEN GORONTALO - Sujarwoko, Sujarwoko; Suprapto, Srihandayani; Karim, Dian Fitriani; Baderan, Umar Sako (Universitas Bina Taruna Gorontalo, 2025)
This study aims to determine the management of Social Assistance (Bansos) in Pentadio Barat Village, Telaga Biru District, Gorontalo Regency. The research method used is qualitative descriptive, in this study data collection through observation, interviews and documentation. The results of the study found that the management of Bansos in Pentadio Barat Village, Telaga Biru District, Gorontalo Regency is not optimal. Of the five evaluation indicators, only the responsiveness indicator is running well, while the other four are not optimal. The Bansos program in Pentadio Barat Village is not fully effective and on target. There is a mismatch in data between the village government and the Social Service, as well as the possibility of multiple recipients of assistance. The adequacy of assistance is also a problem, because the amount of assistance does not meet the daily needs of the community, both in nominal terms and quantity of goods. The distribution of assistance is still constrained by data mismatches, limited quotas from the district, and lack of access to information for the community. The village government needs to improve coordination with the Social Service and improve transparency and effectiveness of data collection. The accuracy indicator in the management of Bansos still faces obstacles, especially in the time of distribution and target recipients. Delays from the central government have an impact on the distribution of aid in villages, so there needs to be improvements in the distribution system to make it more timely and on target.